ESG STRATEGIES, DIGITALIZATION, AND INNOVATION IN THE CONTEXT OF GLOBALIZATION: NEW BENCHMARKS FOR STRATEGIC MANAGEMENT - Рябоволик, Тетяна; Пітел, Наталія (SWorldJournal, 2026)
The article examines the problem of transforming strategic management of enterprises in the context of globalization through the integration of ESG strategies, digitalization, and innovative development. It is substantiated that intensified global compet